Germination tests and plant production of provenances-progenies of Pinus patula - Pérez-Luna, Alberto; Prieto-Ruíz, José Ángel; López-Upton, Javier; Madrid-Aispuro, Rosa Elvira; Salcido-Ruíz, Silvia (BOSQUE, 2024)
The low quality of plants produced in nurseries has added to the high mortality rates in plantations established in Mexico. The objective of this study is to evaluate the effect of three sowing dates and the provenance of the germplasm on the plant quality of Pinus patula, in addition to evaluating the effectiveness of four pre-germination treatments: i) control, ii) soaking in water for 12-hour and storage at 3 °C for five weeks, plus 12-hour soaking before sowing, iii) storage at 3 °C for five weeks and 12-hour soaking before sowing, and iv) 12-hour soaking before sowing. The height, diameter at the root neck, robustness index, and germination efficiency of the provenance progenies of P. patula in the nursery were evaluated, in addition to daily and accumulated germination in the laboratory. Data were analyzed using ANOVA, Kruskal-Wallis tests, Tukey means, and Dunn’s medians. In addition, the response variables were correlated with the bioclimatic variables of the provenances. Statistical differences were found in plant quality according to provenance. Families from Pinal de Amoles, Querétaro presented the lowest robustness index (6,61). The seeds had a higher germination (92,3 %) when soaked for 12 h and stored at 3 °C for five weeks, plus soaking in water for 12 h before sowing. The quality and germination of P. patula are influenced by its provenance, sowing date, and pregerminative treatments.